Physical Education in the Al Quran Perspective - Akbar Yusuf; Halimah Basri; Andi Miswar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Physical education plays a crucial role in shaping human beings holistically, yet in formal educational practice it is often narrowly understood as merely physical activity without the integration of Islamic values. This study aims to examine the concept of physical education from the perspective of the Qur'an, its relationship to physical health and the quality of worship, and its contribution to shaping healthy, strong, and noble individuals. This study uses a qualitative approach of the literature study type with the tafsir mawḍū‘ī method. Data were analyzed from Qur'anic verses, classical and contemporary tafsir literature, hadith, and the views of scholars. The research findings show that the Qur'an views the physical (jasad) and spiritual (rūḥ) dimensions as an inseparable whole. The term